Fucoidan-Mediated Anisotropic Calcium Carbonate Nanorods of pH-Responsive Drug Release for Antitumor Therapy - Wang, Pei; Tong, Fei; Luo, Jun; Li, Zhihua; Wei, Junchao; Liu, Yuangang (Frontiers in Bioengineering and Biotechnology, 2022)
The shape of nanoparticles can determine their physical properties and then greatly impact the physiological reactions on cells or tissues during treatment. Traditionally spherical nanoparticles are more widely applied in biomedicine but are not necessarily the best. The superiority of anisotropic nanoparticles has been realized in recent years. The synthesis of the distinct-shaped metal/metal oxide nanoparticles is easily controlled. However, their biotoxicity is still up for debate. Hence, we designed CaCO3 nanorods for drug delivery prepared at mild condition by polysaccharide-regulated biomineralization in the presence of fucoidan with sulfate groups. The CaCO3 nanorods with a pH sensitivity–loaded antitumor drug mitoxantrone hydrochloride (MTO) showed excellent antitumor efficacy for the HeLa cells and MCF-7 cells in vitro. We believe that anisotropic nanoparticles will bring forth an emblematic shift in nanotechnology for application in biomedicine.